THE INFLUENCE OF IMPLEMENTING A CULTURALLY RESPONSIVE APPROACH TO THE FORMATION OF STUDENTS CHARACTER IN THE CLASS VI - Zulfinar Supriadi; Ali Latif; Arnidah (Media Inovasi Pendidikan dan Publikasi, 2024)
This research is experimental research which aims to determine the influence of implementing a culturally responsive approach on the formation of student character in Class VI of SDN 36 Seppong, North Belopa District, Luwu Regency. The research approach is a quantitative approach. Research data was obtained through observation and tests. The population in the study were all Class VI students at SDN 36 Seppong, North Belopa District, Luwu Regency, totaling 54 students. The sample in the research consisted of 54 students. The data analysis technique is descriptive and inferential statistical analysis. The results obtained in this research are the picture before the application of the culturally responsive approach shows the adequate category and after the application of the culturally responsive approach shows the excellent category and the student's character can be described in the learning results obtained, namely in the pretest they get poor marks while in the posttest they get good marks and the application of the responsive approach Culture has a significant influence on the formation of students' character, especially in Class VI